PENGARUH PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU DI SMKN 1 SANGATTA UTARA - Darajat, Sakia; Paridah, Paridah; Baco, Asmar; Warman, Warman (Penerbit Lafadz Jaya, 2025)
The purpose of this study is to explore the extent to which the implementation of academic supervision by the principal influences the improvement of teacher performance at SMKN 1 Sangatta Utara. Academic supervision is a professional guidance process carried out by the principal to support teachers in improving the quality of learning. This study uses a quantitative method with a correlational approach. The results of the study indicate a significant positive relationship between the implementation of academic supervision and the improvement of teacher performance, especially in the aspects of planning, implementing, and evaluating learning. This finding confirms the importance of the role of the principal as a supervisor in improving the quality of education in vocational schools. The study's findings underscore the critical role of principals in fostering a supportive environment for teacher growth and development. By effectively implementing academic supervision, principals can provide targeted feedback and guidance to teachers, helping them refine their instructional practices and enhance student learning outcomes. Future research could explore specific strategies and best practices for principals to maximize the impact of academic supervision on teacher performance in vocational education settings.